Public Policy and Success of Business Start-ups in Germany - Verena Eckl; Michael Rothgang; Friederike Welter (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
In this paper, we evaluate the success of publicly supported business start-ups by comparing the outcomes of various support measures. Our question is: do business starter get what they need? Since we do not know the needs of the founders we analyse (1) who received which kind of support (financial support, individual coaching, general information) and (2) which kind of support is successful for whom with regard to his/her job history (employed, unemployed or being not part of the job market). While start-up measures possibly could aim at different kinds of eff ects, our focus is on the effect on subsequent firm growth. The analysis is based on a survey conducted in 2005. The sample was drawn from a highly heterogeneous population of business start-ups. By using propensity score exact matching for success measurement we try to capture those differences.
Keywords: J23; M13; C14; 330; Business start-ups; public policy; public support; matching; Unternehmensgründung; Wirtschaftsförderung; Policy-Mix; Erfolgsfaktor; Unternehmensentwicklung; Deutschland